2020
DOI: 10.1136/bmjopen-2020-037664
|View full text |Cite
|
Sign up to set email alerts
|

Use and impact of point-of-care ultrasonography in general practice: a prospective observational study

Abstract: ObjectivesTo describe how general practitioners (GPs) use point-of-care ultrasonography (POCUS) and how it influences the diagnostic process and treatment of patients.DesignProspective observational study using an online questionnaire before and after POCUS.SettingOffice-based general practice.ParticipantsTwenty GPs consecutively recruited all patients examined with POCUS in 1 month.Primary and secondary outcome measuresWe estimated the use of POCUS through the indication for use, the frequency of use, the tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
26
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 22 publications
(30 reference statements)
6
26
0
3
Order By: Relevance
“…Naturally, interns feel it convenient to consult staff. Our survey showed all POCUS examinations were performed for diagnostic purposes which were also consistent with the previous studies [12] which showed the primary aim of performing POCUS was to confirm or disconfirm a specific clinical condition (73.1%). However, some studies [11] illustrated POCUS was used to aid physicians in performing procedureguided ultrasound.…”
Section: Discussionsupporting
confidence: 89%
“…Naturally, interns feel it convenient to consult staff. Our survey showed all POCUS examinations were performed for diagnostic purposes which were also consistent with the previous studies [12] which showed the primary aim of performing POCUS was to confirm or disconfirm a specific clinical condition (73.1%). However, some studies [11] illustrated POCUS was used to aid physicians in performing procedureguided ultrasound.…”
Section: Discussionsupporting
confidence: 89%
“…Recently, a systematic review showed that POCUS is being used frequently in the primary care setting for diagnostic, screening, and procedural use [3]. Additionally, one study has shown that POCUS can influence the diagnostic process in the primary care setting by increasing the confidence of diagnosis and changing management plans [4]. In the inpatient setting, one study has shown that POCUS used during ward emergencies was associated with a shorter time to intervention and decreased mortality when compared to a control group [5].…”
Section: Discussionmentioning
confidence: 99%
“…At the private gynaecologist, the patients can either be clinically managed or be further referred to the hospital. Thus in the intervention, the clinical management of the patients can be completed at the GP, the private gynaecologist, or at the gynaecological department in the hospital [ 24 ]. The completion is denoted with a terminal node.…”
Section: Methodsmentioning
confidence: 99%
“…The cost of ultrasonography scanner and POCUS training are both estimated using depreciation [ 24 , 28 , 29 ]. The cost of having an ultrasonography scanner to examine the patients per scanning is calculated using an average price of an ultrasonography scanner of €15,508.70, the percentage of patients with vaginal bleeding in early pregnancy, an average lifespan of seven years, an interest rate of 4%, and an annual number of ultrasonography scannings of 2.4 per GP.…”
Section: Methodsmentioning
confidence: 99%